RNA Structure Design Improves Activity and Specificity of trans-Splicing-Triggered Cell Death in a Suicide Gene Therapy Approach - Sushmita Poddar; Pei She Loh; Zi Hao Ooi; Farhana Osman; Joachim Eul; Volker Patzel (Elsevier, 2018)
Spliceosome-mediated RNA trans-splicing enables correction or labeling of pre-mRNA, but therapeutic applications are hampered by issues related to the activity and target specificity of trans-splicing RNA (tsRNA). We employed computational RNA structure design to improve both on-target activity and specificity of tsRNA in a herpes simplex virus thymidine kinase/ganciclovir suicide gene therapy approach targeting alpha fetoprotein (AFP), a marker of hepatocellular carcinoma (HCC) or human papillomavirus type 16 (HPV-16) pre-mRNA. While unstructured, mismatched target binding domains significantly improved 3' exon replacement (3'ER), 5' exon replacement (5'ER) correlated with the thermodynamic stability of the tsRNA 3' end. Alternative on-target trans-splicing was found to be a prevalent event. The specificity of trans-splicing with the intended target splice site was improved 10-fold by designing tsRNA that harbors secondary target binding domains shielding alternative on-target and blinding off-target splicing events. Such rationally designed suicide RNAs efficiently triggered death of HPV-16-transduced or hepatoblastoma-derived human tissue culture cells without evidence for off-target cell killing. Highest cell death activities were observed with novel dual-targeting tsRNAs programmed for trans-splicing toward AFP and a second HCC pre-mRNA biomarker. Our observations suggest trans-splicing represents a promising approach to suicide gene therapy.